1994
DOI: 10.1099/00207713-44-2-308
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Evidence for Sphingomonas and Rhizomonas as Nonphotosynthetic Members of the Alpha-4 Subclass of the Proteobacteria

Abstract: Ministq of Agriculture, Forestry and Fisheries, Akitsu, and Faculty of To clarify the taxonomic relationships of the genera Rhizomonas and Sphingomonas, the 16s rFWA sequence of Rhizornonas suberifaciens I F 0 15211T (T = type strain) was determined. A phylogenetic analysis of aligned 16s rRNA gene sequences revealed that eight species of the genus Sphingomonas and R. suberifaciens are closely related to Erythrobacter longus and Porphyrobucter neustonensis and, therefore, belong in the alpha-4 subclass of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
56
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 35 publications
7
56
1
Order By: Relevance
“…The topology of this cluster differed from that in the ARB and BMSB trees, both of which showed this cluster to be included in the lineage of the genus Sphingomonas. The members of this cluster produce pigment (yellow, orange or pink) and mainly contain bacteriochlorophyll a, whereas members of the genus Sphingomonas do not (Shiba & Simidu, 1982;Fuerst et al, 1993;Takeuchi et al, 1994;Yurkov et al, 1994;Denner et al, 2002). Takeuchi et al (2001) also showed that the genus Sphingomonas was related only distantly to the genera Erythrobacter, Erythromicrobium and Porphyrobacter based on 16S rRNA gene sequence similarity, which was 92?9-94?8 %, and the genus Sphingomonas had the presence of one or more oligosaccharide-type glycosphingolipid(s) (GSL) as one of its most characteristic features, whereas the genera Erythrobacter, Porphyrobacter and Erythromicrobium contained monosaccharide-type GSLs only.…”
Section: The Cluster Of the Order 'Sphingomonadales'mentioning
confidence: 99%
“…The topology of this cluster differed from that in the ARB and BMSB trees, both of which showed this cluster to be included in the lineage of the genus Sphingomonas. The members of this cluster produce pigment (yellow, orange or pink) and mainly contain bacteriochlorophyll a, whereas members of the genus Sphingomonas do not (Shiba & Simidu, 1982;Fuerst et al, 1993;Takeuchi et al, 1994;Yurkov et al, 1994;Denner et al, 2002). Takeuchi et al (2001) also showed that the genus Sphingomonas was related only distantly to the genera Erythrobacter, Erythromicrobium and Porphyrobacter based on 16S rRNA gene sequence similarity, which was 92?9-94?8 %, and the genus Sphingomonas had the presence of one or more oligosaccharide-type glycosphingolipid(s) (GSL) as one of its most characteristic features, whereas the genera Erythrobacter, Porphyrobacter and Erythromicrobium contained monosaccharide-type GSLs only.…”
Section: The Cluster Of the Order 'Sphingomonadales'mentioning
confidence: 99%
“…Subsequently, it was found that the genera Sphingomonas and Rhizomonas were also members of the expanding alpha-4 subgroup (21,22). Strain CB81 was designated the type strain of the species by Poindexter (12) and was deposited in the American Type Culture Collection as strain ATCC 15264.…”
mentioning
confidence: 99%
“…Three linker loops (loops [1][2][3] connect the N-and C-domains, and the cleft formed between the two domains is the alginate-binding region, which is larger than that observed in other substratebinding proteins, such as maltose-binding proteins. 25,26) The calcium ion in the C-domain has no function in alginate binding, since the location of the ion is far (about 40 Å ) from the cleft.…”
Section: Alginate-binding Proteinsmentioning
confidence: 99%
“…1) Due to the presence of GSLs, the genus Sphingomonas is classified independently from pseudomonades and is grouped phylogenetically into the -4 subclass of Proteobacteria. 2) Some sphingomonades are characterized by the fact that their cells are covered with many large pleat-like substances 3) and show extraordinary metabolic abilities to degrade various refractory environmental pollutants. 4) These characteristics, inherent to bacteria of this genus, call attention to an unexpected structure and function of the cell surface.…”
mentioning
confidence: 99%